2020
DOI: 10.5539/gjhs.v12n9p60
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey of Factors Influencing Choice of Medical Care Among Ill Patients Suffering from Chronic Diseases in Ebonyi State, Nigeria

Abstract: The cross-sectional survey research design was used to the study the factors influencing choice of medical care among ill patients suffering from chronic diseases in Ebonyi State. The sample of the study comprised 325 in-patients with selected chronic diseases such as diabetics’ mellitus, cardiac and renal diseases who were undergoing treatment at the Federal Teaching Hospital (FETHA 1) Abakaliki. The instrument used for data collection was a 26-item questionnaire developed by the researchers. Data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These labels can be divided into two parts: “hard power” and “soft power.” We innovated to combine the two parts into a score that can show the comprehensive value of the outpatient's choice of hospital. However, most previous studies analyzed the influencing mechanisms about the choice of the hospital just for some provider characteristics they believed were important, 26 , 27 , 28 and the relationship and classification of provider characteristics were not all‐around taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These labels can be divided into two parts: “hard power” and “soft power.” We innovated to combine the two parts into a score that can show the comprehensive value of the outpatient's choice of hospital. However, most previous studies analyzed the influencing mechanisms about the choice of the hospital just for some provider characteristics they believed were important, 26 , 27 , 28 and the relationship and classification of provider characteristics were not all‐around taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies demonstrated that choice or decision to engage or seek a particular medical channel is influenced by a variety of sociodemographic and psychological characteristics, such as age, sex, education, profession, 8,22,23 and the degree of self‐recognition of the disease, 24,25 which we regarded as patients’ internal factors. Moreover, some studies also believed the choice is also based on patients’ external factors regarded as: studies have shown that nonprice and price factors play a significant role in determining the patients choice on services provision which make them be latent utility as an outcome; 4 other studies summarized provider characteristics are structure (the availability of providers, the accessibility of the providers, the type and size of the providers, the availability/experience/quality of the staff, the organization of healthcare, the cost of treatment), process (interpersonal factors, availability of information, continuity of treatment, waiting time, and the quality of treatment), and outcome (mortality or pressure sore rates) 15,26–28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation